Monetary management : [a series of research studies] - Tamagna, Frank M.; Commission on Money and Credit (Englewood Cliffs, N.J., Prentice-Hall, 1963)
This volume was especially prepared for the Commission on Money and Credit as part of its research program leading to the publication in June 1961 of its final report: Money and Credit: their influence on Jobs, prices and growth.
Includes bibliographic references
usc 12/11/18
Loans
Keywords: Monetary policy; United States